2008
DOI: 10.1111/j.1460-9568.2008.06329.x
|View full text |Cite
|
Sign up to set email alerts
|

Truncated tau expression levels determine life span of a rat model of tauopathy without causing neuronal loss or correlating with terminal neurofibrillary tangle load

Abstract: We have previously demonstrated in a transgenic rat model of tauopathy that human misfolded truncated tau derived from Alzheimer's disease suffices to drive neurofibrillary degeneration in vivo. We employed this model to investigate the impact of truncated tau expression levels on life span, neuronal loss and the final load of neurofibrillary tangles (NFTs) in transgenic rats. Two independent transgenic lines (SHR72, SHR318), that display different expression levels of truncated tau, were utilized in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 34 publications
3
58
0
Order By: Relevance
“…These neurons have accumulated large quantities of truncated and hyperphosphorylated tau in the neuronal processes. This finding is consistent with previously published data obtained from in vivo experiments (Koson et al 2008). It will be important to determine whether or not the interneuronal connectivity is compromised in such old cultures.…”
Section: Discussionsupporting
confidence: 95%
“…These neurons have accumulated large quantities of truncated and hyperphosphorylated tau in the neuronal processes. This finding is consistent with previously published data obtained from in vivo experiments (Koson et al 2008). It will be important to determine whether or not the interneuronal connectivity is compromised in such old cultures.…”
Section: Discussionsupporting
confidence: 95%
“…In this study, we focused on truncated t protein, which has been shown to be a driving force behind neurofibrillary degeneration in transgenic rats expressing misfolded truncated t (44,45). We have previously demonstrated that in the transgenic rat brain, neurofibrillary lesions and axonal degeneration are closely associated with the distribution of reactive microglia and macrophages (40).…”
Section: Human Truncated T Stimulates Activation Of Microglia Throughmentioning
confidence: 99%
“…The model expressing non-mutated truncated tau derived from sporadic Alzheimer's disease displayed the ADcharacteristic tau cascade consisting of argyrophilic and phospho-tau positive neurofibrillary tangles, mature sarcosyl insoluble tau complexes and extensive axonal damage in the brain stem and spinal cord. Surprisingly, transgene expression does not cause neuronal loss in the transgenic rat brain (Koson et al 2008). Axonopathy led to neurogenic muscular atrophy, which was the primary cause of progressive muscle weakness.…”
Section: The Rat Models For Human Neurodegenerative Disordersmentioning
confidence: 98%